2017
DOI: 10.1039/c6ra25496a
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the three-dimensional filler structure in a rubber matrix based on fluorescein modified layered double hydroxides

Abstract: A facile fluorescent labeling method was developed to track the filler structural evolution in a rubber matrix, which could be helpful in understanding the Payne effect in the filled compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In addition to the main carbon elements, CB also had other elements, including oxygen, hydrogen, nitrogen, and sulfur, in the form of hydroxyl, carboxyl or other groups. [ 32,33 ] The hydroxyl groups (‐OH) in Zn‐oG‐C 3 could combine with the carboxyl groups on the surface of CB particles. In addition, Zn‐oG‐C 3 is uniformly dispersed in the rubber matrix, which in turn enhances the filler–rubber interaction and consequently reduces the Payne effect, which is a symbol of dynamic heat generation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the main carbon elements, CB also had other elements, including oxygen, hydrogen, nitrogen, and sulfur, in the form of hydroxyl, carboxyl or other groups. [ 32,33 ] The hydroxyl groups (‐OH) in Zn‐oG‐C 3 could combine with the carboxyl groups on the surface of CB particles. In addition, Zn‐oG‐C 3 is uniformly dispersed in the rubber matrix, which in turn enhances the filler–rubber interaction and consequently reduces the Payne effect, which is a symbol of dynamic heat generation.…”
Section: Resultsmentioning
confidence: 99%
“…Lv et al [133] modified the surface of Mg-Al LDH using fluorescein sodium salt (FLU-LDH) and used it to study the nonlinear viscoelastic behaviour and filler structure in SBR. The fluorescent nature of the modifier enabled the authors to visualise the threedimensional filler network structure under strain.…”
Section: Nitrile Butadiene Rubber (Nbr)mentioning
confidence: 99%
“…Table 9 summarises the effect of various LDHs on the properties of SSBR and SBR. The study by Lv et al [133] was omitted as no mechanical property data were explicitly reported. NR can be chemically modified to make ENR.…”
Section: Nitrile Butadiene Rubber (Nbr)mentioning
confidence: 99%